Determining the Mechanism on Ventilation for Thermal Comfort in Residential Buildings: A Case of Government Housing Estates in Nigeria - Ayeni Conqueror Ayoariyo; A. M. O. Atolagbe (New Approaches in Engineering Research Vol. 15, 2021)
Natural ventilation has been agreed to be an energy efficient alternative for reducing the energy use in buildings, achieving thermal comfort and maintaining a healthy indoor environment. The research examines the ventilation system for thermal comfort in residential buildings in a selected government housing estate in south-west Nigeria. In view of this, the study identifies the landscape elements and the level of interest and desirability of users about the use of landscape elements in their environments. There has been little investigation into the mechanisms of ventilation for thermal comfort in residential buildings. According to the survey results, while establishing natural ventilation through such mechanism, 78.0 percent were windows, 12.5 percent soft landscape elements, and 9.5 percent were a mix of window and courtyard. As a result, the study indicated that windows of appropriate size and landscape elements should be used to improve natural ventilation in residential buildings.